Ethyl Acetate Extract of Selaginella doederleinii Hieron Induces Cell Autophagic Death and Apoptosis in Colorectal Cancer via PI3K-Akt-mTOR and AMPKα-Signaling Pathways - Li, Shaoguang; Wang, Xuewen; Wang, Gang; Shi, Peiying; Lin, Shilan; Xu, Dafen; Chen, Bing; Liu, Ailin; Huang, Liying; Lin, Xinhua; Yao, Hong (Frontiers in Pharmacology, 2020)
Colorectal cancer is one type of cancer with high incidence rate and high mortality worldwide. Thus, developing new chemotherapeutic drugs is important. The Selaginella doederleinii Hieron ethyl acetate (SDEA) extract showed good anti-colon cancer effect in vitro and in vivo, but its mechanism is unclear. This study aimed to further reveal the anti-colon cancer effect of SDEA and its possible mechanism. The effects on cell viability, apoptosis, autophagy, and cell cycle in colorectal cells (HT29 and HCT116) were studied using MTT assay, fluorescence microscopy, transmission electron microscopy, and flow cytometry. The mechanisms were further studied using cell transfection, Western blot, and real-time quantitative polymerase chain reaction assay. The effect of xenotransplantation in vivo was observed using immunohistochemistry. Results showed that SDEA inhibited cell proliferation and induced cell morphological changes, cell cycle arrest, autophagy, and apoptosis. It also induced loss of mitochondrial membrane potential, increased the autophagic flux, raised the ratio of Bax/Bcl-2, activated caspases, and inhibited PI3K-Akt-mTOR signaling pathways. Furthermore, SDEA inhibited the growth of xenograft tumors in a dose-dependent manner. Immunohistochemistry analysis confirmed the alteration of autophagy- and apoptosis-related proteins and immunohistochemical microvascular density in xenografts, which were consistent with the results in vitro. Therefore, SDEA is important for developing candidate drugs against colorectal cancers.